2016
DOI: 10.1371/journal.pone.0163001
|View full text |Cite
|
Sign up to set email alerts
|

Enterococcus Species in the Oral Cavity: Prevalence, Virulence Factors and Antimicrobial Susceptibility

Abstract: Enterococci are considered as transient constituent components of the oral microbiome that may cause a variety of oral and systemic infections. As there is sparse data on the oral enterococcal prevalence, we evaluated the Enterococcus spp. and their virulence attributes including antimicrobial resistance in a healthy Brazilian cohort. A total of 240 individuals in different age groups were studied (children 4–11 yrs, adolescents 12–17 yrs, young adults 18–29 yrs, adults 30–59 yrs, elderly over 60 yrs). Oral ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
81
2
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(111 citation statements)
references
References 44 publications
11
81
2
3
Order By: Relevance
“…The multiple antibiotic resistances of our isolates agree with those found in other studies (Rams et al, 2013;Komiyama et al, 2016). The recovery of MDR colonising strains of E. faecium and E. faecalis highlights the ability to these organisms to develop resistance to an array of antimicrobial drugs.…”
Section: Discussionsupporting
confidence: 90%
“…The multiple antibiotic resistances of our isolates agree with those found in other studies (Rams et al, 2013;Komiyama et al, 2016). The recovery of MDR colonising strains of E. faecium and E. faecalis highlights the ability to these organisms to develop resistance to an array of antimicrobial drugs.…”
Section: Discussionsupporting
confidence: 90%
“…Few studies have shown that antibiotic resistant enterococci is transmitted by food [47][48][49] but recently Vidana et al [50] have said there is no food related transmission of enterococci. Enterococci are now showing a high degree of resistance to tetracycline, chloramphenicol, erythromycin besides vancomycin pose a threat for spread of nosocomial infection particularly in patients of ICUs and on mechanical ventilators [51]. Vancomycin resistance is an independent predictor for the overall increase of hospital costs for the patient but also for the individual hospital [52].…”
Section: Oral Infectionsmentioning
confidence: 99%
“…Saphylococcus aureus is also an abundant Gram-positive bacteria which has a strong connection to dental implant infections (Wang and Ren, 2017). Enterococcus faecalis has been connected to oral infections, such as caries, endodontic infections, periodontitis, and peri-implantitis (Komiyama et al, 2016). Controlling these bacteria is of utmost importance in dentistry.…”
Section: Spirulina Platensis Streptococcus Mutans Staphylococcus Aurementioning
confidence: 99%
“…Streptococcus mutans and Staphylococcus aureus are key pathogens that cause infections concomitant with dental caries and dental implants (Wang and Ren, 2017). Enterococcus faecalis has been also related to oral diseases, such as caries, endodontic infections, periodontitis, and peri-implantitis (Komiyama et al, 2016). Thus, it is imperative to find ways for decreasing the bacterial burden of the oral cavity to prevent dental caries and other oral diseases (Wassel and Khattab, 2017).…”
Section: Antimicrobial Efficacies Of Biosynthesized Nanoparticlesmentioning
confidence: 99%